Jenifer Neils and Dylan K. Rogers (eds) The Cambridge Companion to Ancient Athens. - Konijnendijk, Roel (Journal of Greek Archaeology, 2023)
pp. 494 pages, + 56 pages of illustrations and maps in an online supplement. Cambridge: Cambridge University Press, 2021. ISBN 978-1-108-72330-5. £29.99.